2012
DOI: 10.1136/bmjspcare-2012-000196.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of opioids on the phagocytosis of neutrophils and monocytes: a systematic in vitro analysis

Abstract: Background Bacterial infection is a common complication in patients with advanced disease, including cancer. Ingestion (phagocytosis) and subsequent killing of bacteria by neutrophils and monocytes are critical in the control of infection. Using a range of different methodologies, previous invitro and in vivo studies have generally reported that some commonly prescribed opioids are immunosuppressive (ie, morphine), whereas others have been shown to be immunoneutral (ie, fentanyl), and even immunostimulatory (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Freshly isolated peripheral blood monocytes express a relatively low level of CD163, but this expression increases with the differentiation of such cells into macrophages [ 26 ], a role assigned mainly to intermediate monocytes [ 11 , 36 ]. Our results confirm that opioids may substantially affect monocytes’ inactivation, as shown by others [ 38 , 39 ], confirming their anti-inflammatory effect. On the other hand, in patients receiving paracetamol, only an increase in the ratio of CD163/CD206 was detected in non-classic monocytes.…”
Section: Discussionsupporting
confidence: 91%
“…Freshly isolated peripheral blood monocytes express a relatively low level of CD163, but this expression increases with the differentiation of such cells into macrophages [ 26 ], a role assigned mainly to intermediate monocytes [ 11 , 36 ]. Our results confirm that opioids may substantially affect monocytes’ inactivation, as shown by others [ 38 , 39 ], confirming their anti-inflammatory effect. On the other hand, in patients receiving paracetamol, only an increase in the ratio of CD163/CD206 was detected in non-classic monocytes.…”
Section: Discussionsupporting
confidence: 91%
“…31 Codeine does not produce a detectable influence on immune responses. 32 As mentioned above, the dose of codeine used (10 mg) was lower than its analgesic dose (ranging from 15 to 60 mg), thus, it is also reasonable that codeine dose was not as analgesic as it could be. This would normally occur in a disease of lesser intensity, but as there is an intense inflammatory response in Covid-19, the standard dose may not have been sufficient to reduce the production of the biological markers evaluated, and consequently, interfere with the pain perception.…”
Section: Discussionmentioning
confidence: 97%
“…In general, most of the studies demonstrated morphine suppresses the production of cytokines by macrophages and T cells 31 . Codeine does not produce a detectable influence on immune responses 32 . As mentioned above, the dose of codeine used (10 mg) was lower than its analgesic dose (ranging from 15 to 60 mg), thus, it is also reasonable that codeine dose was not as analgesic as it could be.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, codeine, oxycodone, diamorphine, and methadone did not produce a measurable effect on the immune system [ 19 ]. Another related study indicated that morphine leads to the induction of apoptosis in the immune cells, atrophy of the thymus and spleen, and suppression of proliferation of B and T lymphocytes [ 20 ].…”
Section: Main Bodymentioning
confidence: 99%